2016
DOI: 10.3109/09537104.2016.1171302
|View full text |Cite
|
Sign up to set email alerts
|

Platelet phenotype changes associated with breast cancer and its treatment

Abstract: Platelets and their granular contents influence both angiogenesis and breast cancer progression. This study was performed to assess the effect of breast cancer and its treatment on platelet biology and the response to inhibition of the platelet P2Y12 receptor. Receptor-specific platelet activation and inhibition was studied for three platelet-associated proteins important in cancer angiogenesis and progression, vascular endothelial growth factor (VEGF), thrombospondin1 (TSP1), and transforming growth factor be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The assessment of short-term effects of aspirin from the analyses of 51 randomized controlled trials that were designed to evaluate the role of aspirin in the primary and secondary prevention of vascular events demonstrated that aspirin reduced the incidence of several cancers from 3 years onwards [ 104 ]. In addition to having a preventive role in cancer, depending on the duration of treatment, aspirin also improves the results of treatment among cancer patients [ 7 , 17 , 24 ].…”
Section: Platelet-associated Molecules and Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…The assessment of short-term effects of aspirin from the analyses of 51 randomized controlled trials that were designed to evaluate the role of aspirin in the primary and secondary prevention of vascular events demonstrated that aspirin reduced the incidence of several cancers from 3 years onwards [ 104 ]. In addition to having a preventive role in cancer, depending on the duration of treatment, aspirin also improves the results of treatment among cancer patients [ 7 , 17 , 24 ].…”
Section: Platelet-associated Molecules and Therapymentioning
confidence: 99%
“…The differences in results may be associated with the length of time aspirin is taken [ 17 ] Shiao]. A prospective observational study of 4164 women with breast cancer showed that decreased risk of distant recurrence and breast cancer death is observed when aspirin is taken at least 12 months [ 7 ]. The newest retrospective analysis of 222 stage II and III triple-negative breast cancer (TNBC) patients demonstrates improvement in 5-year DFS (80.1 vs 62.6%, p = 0.04) and 5-year DMR (9.0 vs 31.6%, p = 0.007) in the aspirin group compared with the control group.…”
Section: Platelet-associated Molecules and Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study performed on twenty-four women with active breast cancer and ten healthy controls showed that breast cancer and its chemotherapeutic treatment influence platelet phenotype, by increasing VEGF release and modulating the response to antiplatelet therapy [119]. Noticeably, an autocrine-paracrine loop, occurring in the bone marrow microenvironment and involving VEGFR-1-dependent megakaryocyte maturation has been documented [120]. Such evidence, together with the finding that tumor-derived IL-6 leads to enhanced megakaryocyte VEGF expression and a higher platelet VEGF load (concomitantly associated with fast tumor growth kinetics and poor diagnosis), strongly suggest a cooperation between platelets and cancer in promoting angiogenesis [121].…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%